The Influence of the Vanishing Twin on the Perinatal Outcome of Surviving Singleton in IVF Pregnancy - Li, Jiarong; Li, Jingyu; Zhang, Yiyuan; Hu, Kuona; Chen, Na; Gao, Jie; Hu, Jingmei; Cui, Linlin; Chen, Zi-Jiang (Frontiers in Endocrinology, 2022)
Objective: The purpose of this study was to clarify the influence of the vanishing twin (VT) on the perinatal outcomes in the surviving singleton, and further identify the susceptible window. Study design: Retrospective cohort study. Methods: A total of 636 survivors of a vanished co-twin and 11148 singleton controls were enrolled. The exposed group was further divided into early VT (EVT, VT≤13 weeks, N=593) and late VT subgroups (LVT, VT>13 weeks, N=43) according to the gestational age of the twin vanishing. All participants were conceived through in vitro fertilization (IVF). Perinatal outcomes including gestational age, birthweight, and the incidence of preterm birth(PTB), low birthweight (LBW), small for gestational age (SGA), neonatal intensive care unit (NICU) admission, umbilical cord abnormality, jaundice of the newborn and oligohydramnios were compared among the groups. Results: In our birth cohort, about 5.4% of all singleton deliveries were originated from vanishing twin pregnancies. Compared with the singletons, both early and late VT pregnancy had a significantly lower birth weight (3336.28±533.44 g and 2985.92±772.22 g vs 3446.06±526.12 g; P<0.001 and P<0.001), more frequent neonatal jaundice (47.0% and 60.5% vs 40.6%; P=0.002 and P=0.008), and decreased incidence of umbilical cord abnormality (15.5% and 7.0% vs 19.9%; P=0.009 and P=0.034). Newborns in early VT group were more likely to manifested as SGA (5.4% vs 3.6%, P=0.002) and suffered oligohydramnios (5.4% vs 3.4%; P=0.009) than the primary singletons. In addition, the gestational age of late VT survivors were shorter than the controls (37.25±3.25 vs 39.04±1.63, P=0.001), and had a significantly higher risk of PTB (30.2 % vs 6.6%; P<0.001) and NICU admission (27.9% vs 9.4%, P<0.001). All differences except for SGA maintain significant after adjusted for maternal age, BMI and parity. Conclusions: Singletons with a vanished co-twin had worse perinatal outcomes compared with the original singletons. LVT burden even much on the survival one. Therefore, close monitoring during perinatal period was suggested in this type of neonates. And elective single embryo transfer should be also fully considered which could tackle the problem at its root.